A User Profiling Architecture for Textual-Based Agents - Godoy, Daniela Lis (2002)
Several intelligent agents have been developed in the last decade to help users with the increasing volume of information available in the WWW. Despite the efficiency of these agents depends on the knowledge they have about users, which is contained into user profiles, there are diverse considerations about what a profile should contain and how to construct it. Due to this fact, developers have to face the problem of specify each time, not only the content of user profiles, but also how to acquire it and how to adapt it to changes on user interests. In this work we present an architecture which prescribe these aspects of the user profiling task. The goal of this architecture is to guide developers in the construction of agents involved with textual-based tasks. The results obtained from its application in a search agent are also report in this work.